Improving the Knowledge of Women Farmers Group (KWT) on Drip Irrigation System: Innovation in Water Use Efficiency for Sustainable Agriculture in Bandingan Village, Rakit, Banjarnegara: Peningkatan Pengetahuan Kelompok Wanita Tani (KWT) terhadap Sistem Irigasi Tetes : Inovasi Hemat Air untuk Pertanian Berkelanjutan Di Desa Bandingan, Rakit, Banjarnegara - Eka Oktaviani; Isnaendi Agung Abadi; Fifi Nafisah; Ravi Izza Alfani; Galuh Muthia Dewi; Anisa Nur Afni Rahmadhani; Nadya Riezqi Rahman (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2026)
Bandingan Village, Rakit District, Banjarnegara Regency, Central Java Province, has dry lands, resulting in relatively low agricultural productivity. Given these conditions, the drip irrigation system is an alternative solution for efficient water use. The community service activity on the socialization of the drip irrigation system was aimed to increase the knowledge of the women farmers group (KWT) regarding the application of the drip irrigation system. This activity was part of the Community Service Program of Universitas Jenderal Soedirman for the period July - August 2025, which have been carried out through initial observation, assesment (pre-test), the transfer of knowledge about the drip irrigation system, discussions, practices, then final assessment (post-test), and as well as analysis data of the evaluation. Eighteen members of the women farmers group actively participated in this program. Data analysis was carried out using a paired T-test in Microsoft Excel. Overall, the data analysis showed a significant increase in knowledge after the socialization, particularly in understanding (definition), advantages (benefits), tools used for installation, and how drip irrigation works. The increase in knowledge of drip irrigation was 95.83%, the benefits aspect reached 90.28%, the knowledge aspect regarding installation tools was 100%, and the aspect regarding how it works was 88.33%. Thus, this activity increases public knowledge about the concept, benefits, and application of the technology. This knowledge can be applied to improve water use efficiency in the agricultural land that tends to be dry in this village.